A lifespan perspective on transitions during a top sports career: A case of an elite female fencer - Debois, N.; Ledon, A.; Argiolas, C.; Rosnet, E. (Psychology of Sport and Exercise, 2012)
Objectives: The purpose of this study was to explore how an elite female fencer with Olympic goals dealt with key events and transitions in her sports career as well as with other domains of her life. Method: A narrative approach was adopted consisting of reconstructing, then analysing, the single-case athlete's story with data collected over a period of fourteen years, from a retrospective in-depth interview conducted at the end of the sports career as well as from handwritten notes taken during sixty-one invivo interviews conducted for assessment, follow-up or psychological counselling during the athlete's sports career. Results: Qualitative analysis revealed a non-linear path to excellence with alternative positive and crisis transitions framing three main stages related by the athlete: (a) a stage of equilibrium between family life, sports and studies, (a) a stage of primacy to sports career and, (c) a stage of stability due to living as part of a couple. The athlete's story also emphasized the importance of taking into account the socio-cultural and sport system context in which an Olympic career takes place, as well as other domains of athletes' life (i.e., personal and social life, educational and vocational development). Conclusion: This study provided an illustration of the ups and downs that elite athletes may face in their pursuit of excellence and invites questions about the conditions which would best contribute to the effectiveness of psychological intervention for enhancing both performance and personal growth.